2004
DOI: 10.1002/uog.1032
|View full text |Cite
|
Sign up to set email alerts
|

Fetal heart rate and umbilical artery flow velocity variability in intrauterine growth restriction: a matched controlled study

Abstract: K E Y W O R D S:blood flow velocity variability; fetal growth restriction; heart rate variability ABSTRACTObjectives To study heart rate and umbilical artery blood flow velocity variability in growth-restricted fetuses and investigate the influence of the autonomic nervous system on these parameters. Methods Conclusion Flow velocity variability in growth restrictionseems not to be predominantly influenced by the autonomic nervous system, whereas the decreased heart rate variability seems to be influenced by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
(30 reference statements)
1
20
0
1
Order By: Relevance
“…It has been suggested that the sympathetic nervous system is more affected than parasympathetic tone in FGR . This is a possible explanation for the delayed appearance of accelerations, and could also justify the finding of a lower baseline at certain gestational ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the sympathetic nervous system is more affected than parasympathetic tone in FGR . This is a possible explanation for the delayed appearance of accelerations, and could also justify the finding of a lower baseline at certain gestational ages.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies on FGR that display data on CTG parameters, present findings irrespective of gestational age, despite the great heterogeneity of individuals regarding this aspect. 3,5,6,[14][15][16][17][18][19][20][21][22][23] Moreover, the few studies presenting results by gestational age include a small number of FGR cases. 4,24,25 Therefore, the influence of gestational age on CTG in FGR has never been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ratio between low-frequency and high-frequency HRV may represent sympathovagal balance. Growth-restricted fetuses were found to have reduced lowfrequency/high-frequency ratio, which could be caused by increased parasympathetic activity as part of an energy preservation strategy when exposed to chronic oxygen and nutrient deprivation (60,66). In support of this, growth-restricted fetuses display less movements (67) and spend more time in aIMT, aortic intima media thickness; BP, blood pressure; BW, birth weight; Ca, corrected age; cIMT, carotid intima media thickness; eFW, estimated fetal weight; Ga, gestational age; hR, heart rate; IUGR, intrauterine growth restriction; N/a, not available; PNa, postnatal age.…”
Section: Sympathovagal Balance In Growth-restricted Fetuses and Infantsmentioning
confidence: 99%
“…A decline in fetal HRV is thought to indicate fetal compromise. Several studies have shown reduced HRV in growth-restricted fetuses compared to AGA peers, indicating that these fetuses are compromised by the unfavorable intrauterine environment (59)(60)(61)(62). Moreover, lowered HRV has been clearly associated with fetal acidemia and hypoxia (63).…”
Section: Hrv In Growth-restricted Fetuses and Infantsmentioning
confidence: 99%
“…It was possible to speculate the approximately identical contribution of the above-mentioned controlling signals to the umbilical venous hemodynamics. The peak with the frequency of about 0,5 Hz is found also in the total power spectrum of blood flow velocity variability in the umbilical artery (24). It was suggested that the maternal RSA played a significant role in the umbilical hemodynamics and supported a continuous non-pulsatile pattern of the venous blood flow.…”
Section: Discussionmentioning
confidence: 90%